An operator defined by convolution involving the generalised Hurwitz-Lerch zeta function - Aabed Mohammed,; Maslina Darus, (Universiti Kebangsaan Malaysia, 2012)
In this article, we studied the generalised Hurwitz-Lerch zeta function. We defined a new operator and introduced a new class of function. Here, some interesting properties and sufficient conditions for subordination were also studied.